PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN BONGGOL JAGUNG MENJADI JAMUR BONGGOL DI DESA JAMBESARI - Qoidul Khoir (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Weevil mushrooms are a type of mushroom that has high economic value and is very promising as a source of income for mushroom farmers. As the demand for humpback mushrooms increases, business opportunities for humpback mushrooms have high prospects. Based on this, there is a need to empower the community regarding the production or cultivation of Weevil Mushrooms in Jambesari Village. The aim of this service program is to provide education and assistance to the Jambesari Village Community regarding how to cultivate humpback mushrooms from the process of preparing ingredients to the process of harvesting humpback mushrooms. This tuber mushroom cultivation business is used to improve the community's economy and make it a superior product. The results of community service in the production of tuber mushrooms are: 1). Mitra was able to make a growing medium for weevil mushrooms by utilizing corn cob waste which is abundant, cheap and easy to obtain from the surrounding environment, namely corn cobs which some people throw away after going through the corn selep process 2). The creation of a community as cadres who have expertise in the tuber mushroom cultivation business. 3). Increased knowledge in the community that tuber mushroom products, apart from being able to be used to add nutrition or food menus, can also increase family income.